O governo de menores de idade em relação à prática da prostituição: os discursos de agentes sociais - Molina, Ana Maria Ricci (Universidade Federal de São Carlos, 2014)
In the field of prostitution children and adolescents can be found, although considered a social practice that violates their rights. Consequently, society has created a social network of care, where the Guardian Council and the Specialized Care Program Families and Individuals to combat this violation. However, it seems that the government held by social agents of these instances denotes security mechanisms and risk management through a series of practices called menoristas and minors in order to resonate the notion of deviance as a facilitator of the violation of rights and the body by the subject. The questioning of such practices points to the tension between the sovereignty of the individual and technical rationality, and also with the moral values concerning sexual absurdity and good social order. At the end, appear the silence of society, the politics of social agents and the resistance of children and adolescents in the face of commercial sexual exploration. This analysis was possible by reading the records of commercial sexual exploration of children and adolescents the existing Guardianship Council (years 1994, 2005 and 2011) PAEFI-Sentinela (2005 and 2011), both the city of Ribeirão Preto / SP, based the genealogical method and the theories about government, sexuality and abnormality presented by Michel Foucault and followers.
Keywords: Prostituição; Infância e juventude; Sexualidade; Governo; Prostitution; Childhood and youth; Sexuality; Government; CIENCIAS HUMANAS::EDUCACAO